POLA KOMUNIKASI DINAS KEBUDAYAAN, PARIWISATA, PEMUDA DAN OLAHRAGA KABUPATEN INDRAGIRI HILIR DENGAN MASYARAKAT SUKU DUANO DALAM MENGEMBANGKAN BUDAYA FESTIVAL MENONGKAH KERANG - Riski Mainaki Pasesa; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Cutting shells is an activity to catch shells on the stretch of mudflats of the Indragiri Hilir coast. This unique and rare activity at a glance looks like surfing. Using a board like a real surfboard, but the objects and techniques are far different. This activity was lifted from the culture of the persistent "sea people" Duano people who inhabit Indragiri Hilir Regency. The Duano people live on houseboats, wandering from place to place at sea level. At present, the Duano community has experienced an increase in civilization. Ordinary people and the Government of Indragiri Hilir Regency have begun to get rid of the thought of the Duano tribality, starting from the natural wealth it has, its culture, and its human resources that can produce great potential, one that the Duano tribe is proud of is the Scallop Menongkah Festival. This study aims to determine the communication patterns of the Office of Culture, Tourism, Youth and Sports of Indragiri Hilir Regency with the Duano people in developing the culture of the shellfish-eating festival. In this study the authors used the theory of communication patterns according to Effendy, namely: 1) Primary Communication Patterns, 2) Secondary Communication Patterns, 3) Linear Communication Patterns, and 4) Circular Communication Patterns.The research method used is descriptive qualitative data collection techniques of observation, interviews and documentation. The data in this study are Primary and Secondary. Data analysis techniques in this study were carried out in several stages, namely: 1) Data Collection, 2) Data Reduction, 3) Data Presentation, and 4) Drawing Conclusions.The results showed that po the most influential communication of the four patterns above is the pattern of linear communication / direct communication with the Duano people. This is caused by several factors including the lack of telecommunications networks at that time. So that the Office of Culture, Tourism, Youth and Sports of Indragiri Hilir Regency needs to conduct face-to-face meetings with the Duano people. However, it should be noted that every communication pattern carried out has its own goals and benefits.